A relationship between preoperative anxiety and postoperative pain in odontectomy patients under general anesthesia at Moewardi Regional General Hospital - Mursyid, Farhandika; Septiawan, Debree; Lisetiawati, Lisetiawati (Majalah Kedokteran Gigi Indonesia, 2024)
Odontectomy is a surgical procedure to extract impacted teeth and also commonly performed to address dental and oral health issues. One symptom observed prior to the procedure is anxiety that may cause patients to avoid dental care. One effect attributed to preoperative anxiety in odontectomy patients includes a decrease in pain control, encompassing postoperative pain, possibly through Hypothalamic-Pituitary-Adrenal (HPA) axis. Postoperative pain itself is a complex issue requiring effective management to ensure good healing. This study aimed to determine the relationship between preoperative anxiety and postoperative pain in odontectomy patients under general anesthesia at Moewardi General Hospital and to measure the relationship between preoperative anxiety and postoperative pain intensity in patients undergoing odontectomy under general anesthesia at Moewardi General Hospital. This was a cross-sectional study of which the data were obtained through interviews. A total of 30 samples were selectedfrom the Dental and Oral Outpatient Clinic at Moewardi General Hospital scheduled for odontectomy under general anesthesia from December 2022 to January 2023. The Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire and Visual Analogue Score for Pain were used respectively to measure preoperative anxiety and postoperative pain. Statistical analysis of the relationship was conducted using the Pearson Correlation Test to assess the strength of the relationship. The average preoperative anxiety level was 17.17 and the postoperative pain intensity was 3.93 with the correlation coefficient of 0.587 (p < 0.05), indicating that the relationship fell within moderate and significant category. Preoperative anxiety exhibited a moderate and significant correlation with postoperative pain in odontectomy patients under general anesthesia.